Physical education of children in pre-primary education in Ukraine (pedagogical aspect) - Władimir Pasicznik (Jan Długosz University in Częstochowa, 2022)
This article is devoted to the issues of physical education in preschool education in Ukraine. The organisation of physical education process in kindergartens in this country is conducted in accordance with the regulation of the Ministry of Education and Science of Ukraine "On preschool education" and with the state educational programmes "Child", "Ukrainian preschool", "Little Seed", "Toddler", "Pre-school Child", "Me in the World". Physical games, morning gymnastics, Health Days, Sports Days and walking trips play an important role in physical education of preschoolers in Ukraine. The main tasks of physical education in Ukraine in preschool institutions are: strengthening the health of children; fostering the harmonious development of the organism; development of motor skills; body hardening; forming hygiene habits. In the recent years, an increase in the interest in using the resources of folk physical culture in physical education classes has been observed in the activities of Ukrainian preschools. The position of a physical education teacher has been introduced in preschool education institutions. The basic organisational forms of conducting physical education classes in preschools in Ukraine include: frontal form, classes in teams, additional activities. An important element of the effectiveness of physical education of preschool children in Ukraine is the integration of physical education forms with music and dance.